Extracellular vesicles from human saliva promote hemostasis by delivering coagulant tissue factor to activated platelets - Yu, Y.; Gool, E.; Berckmans, R.J.; Coumans, F.A.W.; Barendrecht, A.D.; Maas, C.; van der Wel, N. N.; Altevogt, P.; Sturk, A.; Nieuwland, R. (Journal of thrombosis and haemostasis, 2018)
Essentials Human salivary extracellular vesicles (EVs) expose coagulant tissue factor (TF). Salivary EVs expose CD24, a ligand of P‐selectin. CD24 and coagulant TF co‐localize on salivary EVs. TF+/CD24+ salivary EVs bind to activated platelets and trigger coagulation. Summary Background Extracellular vesicles (EVs) from human saliva expose coagulant tissue factor (TF). Whether such TF‐exposing EVs contribute to hemostasis, however, is unknown. Recently, in a mice model, tumor cell‐derived EVs were shown to deliver coagulant TF to activated platelets at a site of vascular injury via interaction between P‐selectin glycoprotein ligand‐1 (PSGL‐1) and P‐selectin. Objectives We hypothesized that salivary EVs may deliver coagulant TF to activated platelets via interaction with P‐selectin. Methods We investigated the presence of two ligands of P‐selectin on salivary EVs, PSGL‐1 and CD24. Results Salivary EVs expose CD24 but PSGL‐1 was not detected. Immune depletion of CD24‐exposing EVs completely abolished the TF‐dependent coagulant activity of cell‐free saliva, showing that coagulant TF and CD24 co‐localize on salivary EVs. In a whole blood perfusion model, salivary EVs accumulated at the surface of activated platelets and promoted fibrin generation, which was abolished by an inhibitory antibody against human CD24. Conclusions A subset of EVs in human saliva expose coagulant TF and CD24, a ligand of P‐selectin, suggesting that such EVs may facilitate hemostasis at a site of skin injury where the wound is licked in a reflex action.